Using experience-based co-design to explore care experiences and identify practice change priorities for children with medical complexity in the paediatric intensive care unit - Eyal Cohen; Kenneth Southall; Hema Patel; Karen Dryden-Palmer; Susan Law; Francine Buchanan; Franco Carnevale; Patricia Fontela; Saleem Razack; Isabelle St-Sauveur; Janet E Rennick; Maryse Dagenais; et al. (BMJ Open)
Objectives Children with medical complexity (CMC) frequently experience acute deterioration requiring paediatric intensive care unit (PICU) hospitalisation. Collaboration between families and healthcare professionals (HCPs) is vital yet often challenging, suggesting a new care approach is needed. This study explored the PICU care experiences of CMC, parents and HCPs and identified common priorities and practice changes to enhance care.Design An experience-based co-design (EBCD) approach was used. Semistructured interviews were conducted with CMC and parents (stage 1) and HCPs (stage 2). A co-design event with parents and HCPs followed (stage 3).Setting Interviews took place in family homes, hospital meeting rooms and virtually. The co-design event took place at the hospital.Participants Interviews: CMC and parents (n=21, 13 families) within 1 year of their most recent PICU discharge. PICU and complex care service HCPs (n=15). Co-design event: parents and HCPs (n=22). Maximum variation sampling was used.Results Stage 1: Child and family-related themes included becoming known, becoming a parent caregiver or child care receiver, establishing caregiver relationships, and expecting a responsive and dignified caregiving environment. Stage 2: HCP-related themes included adapting to a different care approach, positioning parents as collaborators, navigating personal connections, and providing continuity of care. Stage 3: Two videos (sharing child and family perspectives, and HCPs’ perspectives) were produced to promote discussion at the co-design event. Common care priorities included increase HCPs’ awareness of who the child is when they are well; improve interdepartmental communication; enhance HCPs’ understanding of families’ expertise and needs; enhance parent-HCP partnerships and develop HCP training programmes. Potential practice changes were identified.Conclusions Participants identified the need for a collaborative approach to care for critically ill CMC, integrating the expertise of children, parents and HCPs. EBCD can help ground the perspectives and needs of HCPs, children and families in future PICU patient and family-centred care interventions.